Withanolide a penetrates brain via intra-nasal administration and exerts neuroprotection in cerebral ischemia reperfusion injury in mice - Mukherjee S.; Kumar G.; Patnaik R. (My University, 2025)
1. Withanolide A (WA), a major constituent phytochemical of the Ayurvedic herb Withania somnifera reportedly combats neurodegeneration in Alzheimer’s disease and Parkinson’s disease. But no study has yet reported the ability of WA in crossing the blood–brain barrier (BBB). The present study analyses the brain penetration ability of WA after intra-nasal administration and assesses its neuroprotective ability in cerebral ischemia-reperfusion injury in adult mice model. 2. Brain penetration of WA after intranasal administration in cortex and cerebellum was assessed using HPLC-UV. Three different doses (1 mg/kg, 5 mg/kg and 10 mg/kg) of the phytochemical were used to study the neuroprotective ability of WA by evaluating the brain damage, changes in cerebral neurotransmitter levels and brain tissue morphology. 3. Intranasal administration of the phytochemical facilitates its penetration in the cortex and cerebellum. Post-treatment with WA significantly reduced cerebral infarction, restored BBB disruption and cerebral oedema. The WA post-treatment also lowered the ischemia-induced elevated neurotransmitter and biochemical levels in brain compartments. The highest dose (10 mg/kg) of WA also markedly reduced the morphological damages, apoptotic and necrotic cell death in brain tissue occurring due to cerebral ischemia pathophysiology. 4. Intra-nasal administration enables brain penetration of WA and allows the phytochemical to exert neuroprotective ability in the global cerebral ischemia model. © 2020, © 2020 Informa UK Limited, trading as Taylor & Francis Group.